Test-driven development for JavaScript - Olsen, Andy (Addison-Wesley Professional, 2022)
10+ Hours of Video Instruction Learn How to Use Test-Driven Development Techniques to Create High-Quality JavaScript Applications Overview Test-Driven Development for JavaScript LiveLessons brings you step-by-step knowledge to create high-quality JavaScript applications. The course teaches you how to apply test-driven technologies to create reliable and verifiable JavaScript solutions that are maintainable and adhere to best practices. JavaScript has become an indispensable language in modern-day computing. Writing JavaScript is relatively straightforward but writing high-quality JavaScript and testing it thoroughly is much harder. Test-Driven Development for JavaScript LiveLessons uses Jest for defining and running JavaScript and TypeScript tests. It also covers how to use Jest to test many popular types of JavaScript solutions, including Node.js applications on the server and React and Angular solutions at the client. Taught by experienced trainer and author, Andy Olsen, this course is your complete guide to mastering writing high-quality JavaScript. The course has hands-on demos throughout the lessons for better understanding of the topic areas. About the Instructor Andy Olsen is a freelance consultant, instructor, and developer with more than 30 years of experience in IT. Andy began his professional career as a C/C++ developer and morphed into Java, C#, and other languages as the years passed by. He is actively involved in a wide range of technologies including full stack development, cloud native applications, data science, and more. He is passionate about technology education and runs training courses around the world across diverse market sectors. You can find Andy here: https://www.linkedin.com/in/andy-olsen-481496/ http://olsensoft.com/ Skill Level Intermediate Learn How To Set up a testing environment for JavaScript and TypeScript Organize tests into suites Write effective tests for the user interface and for server-side code Apply mocking techniques effectively Test React applications Test Angular applications Who Should Take This Course Individuals implementing client-side JavaScript web clients or server-side Node.js applications Course Requirements JavaScript programming experience, either creating client-side web applications or server-side Node.js applications About Pearson Video Training Pearson publishes expert-led video tutorials covering a wide selection of technology topics designed to teach you the skills you need to succeed. These professional and personal technology videos feature world-leading author instructors published by your trusted technology brands: Addison-Wesley, Cisco Press, Pearson IT Certification, Sams, and Que Topics include: IT Certification, Network Security, Cisco Technology, Programming, Web Development, Mobile Development, and more. Learn more about Pearson Video training at http://www.informit.com/video.
Online resource; title from title details screen (O'Reilly, viewed July 12, 2022)
Keywords: Application software -- Testing; Application software -- Development; Java (Computer program language); Logiciels d'application; Développement; Java (Langage de programmation); Application software; Development; Application software; Testing; Instructional films; Internet videos; Nonfiction films; Films de formation; Films autres que de fiction; Vidéos sur Internet